2016
DOI: 10.2514/1.t4550
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nonequilibrium Air Plasma Radiation Behind a Shock Wave

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…This is of interest, as work by Lemal et al. (2016) reproduced this ‘dip’ feature (where other models did not) for vacuum ultraviolet atomic radiance at similar test conditions to those that are presented here. That analysis did not include deceleration effects, and only considered thermochemical modelling – specifically, various heavy-particle impact excitation models were applied.…”
Section: Shock Deceleration Effects On Test Slug Morphologysupporting
confidence: 79%
“…This is of interest, as work by Lemal et al. (2016) reproduced this ‘dip’ feature (where other models did not) for vacuum ultraviolet atomic radiance at similar test conditions to those that are presented here. That analysis did not include deceleration effects, and only considered thermochemical modelling – specifically, various heavy-particle impact excitation models were applied.…”
Section: Shock Deceleration Effects On Test Slug Morphologysupporting
confidence: 79%
“…Figure shows the results of heavy-particle impact excitation rate measurements as well as theoretical predictions on an Arrhenius plot. Although a few estimates exist for electronic excitation rates due to N–N, N–O, and O–O collisions (relevant to high-temperature air CR models , ), to the authors’ knowledge, these are the first direct shock tube measurements of O* formation rates by O–Ar collisions. Best fits of the current experiments were obtained using the format k M (1, i ) = A T b exp­(− C / T ), where the temperature dependence term b was fixed at 1/2 to match the dependence from the theoretical formulation, the activation energy term C was set to E i (in K), and the best fit was determined by varying the parameter A .…”
Section: Shock Tube Experimentsmentioning
confidence: 99%
“…In their study, they found that heavy-particle impact processes (N−N, N−O, O−O collisions) may play a significant role in the electronic excitation immediately after passage of the incident shock, where the gas is weakly ionized and electrons are scarce. Although this work focused particularly on the electronic excitation of atomic oxygen (a major constituent of high-temperature air) by argon at a lower-temperature regime (T < 8000 K), the weakly ionized nature of the flow suggests, analogously to Lemal et al, 24,25 that heavy-particle impact O−Ar collisions could play a dominant role in the production of O* over O−e − collisions when temperatures are "low".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the surface temperature of a hypersonic vehicle may reach 2000 K with a non-uniform distribution [23]. The TIR emission can also be radiated from gases in the shock layer and wake flows [24]. This means that the temperature of both the aircraft's surfaces and the reacting flows may influence the evaluation of infrared optical observability.…”
Section: Introductionmentioning
confidence: 99%